MANAGING SUPPLY CHAIN RISK OF PERISHABLE GOODS: PERSPECTIVE FROM SMALL TO MEDIUM-SIZED TOFU FIRM IN A DEVELOPING COUNTRY - Mahbubah, Nina Aini (SIGMA TEKNIKA, 2025)
Tofu producer is a small and medium enterprise that produces white tofu in the food industry. In supply chain activities, many risks still disrupt the smooth running of industrial activities. These risks or disruptions include delays in the delivery of soybean raw materials, business owners having difficulty planning raw materials, disruption of the production process due to machine damage, and various other potential risks. Based on this, this research identified risk events and causes of risk events, as well as proposed mitigation actions that could be applied using the House of Risk (HOR) method. The research found 19 risk events and 20 risk risk agents. HOR 1 phase findings include that insufficient maintenance management posed the most significant risk. The poor maintenance led to the highest overall Risk Potential score. The HOR 2 calculation identified nine mitigation to minimize risks throughout the supply chain process